O objeto do contrato - Gomes, Susete (2008)
This work examines the object of the contract, in the bilateral, commutative, and parity contract. The initial point is the perspective of the contract as expression of the private autonomy, and, that way, the parts should use the best communication in order to establish the contract program. For that, it is necessary to understand the importance of the language in such a context, especially because the complexity of the modern life imposes selectivity. When establishing a certain contract program, one choice among many other possibilities is made. In order to verify the study dimension of the object of the contract, analyzing the institutes of the private autonomy is need, as well as juridical business, contracts and contract principles. Existence and validity requirement presuppose the object of the contract, which has effects in the phenomenic world of the Law. The object of the contract should be understood both as the content (contract program) and as the objective (purpose). It differs from the cause of the contract and from the consensus. It should also be seen as a composite of obligations, duties, rights, responsibilities, subjections, and it should be seen as an unit. In that sense, it is not confused with object of the obligation, nor of the obligation, nor of the duty. All those elements integrate the object of the contract. The object can suffer vicissitudes along the contract relation, and, for that reason, it requires contractual balance to be protected, be it in a preventive way and in the private autonomy scope, be it through the system that supplies mechanisms to recompose the contract program balance, which allows the purpose of the contract to be reached